2017
DOI: 10.3390/ijgi6090283
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modelling and Prediction Assessment of Soil Iron Using Kriging Interpolation with pH as Auxiliary Information

Abstract: Abstract:In this study, different interpolation techniques are presented, assessed, and compared for the estimation of soil iron (Fe) contents in locations where observations were not available. Initially, 400 soil samples from the Kozani area, which is near Polifitou Lake in northern Greece, were randomly collected from 2013 to 2015 and were analysed in the laboratory to determine the soil Fe concentrations and pH. The soil Fe concentrations were examined for spatial autocorrelation, and semivariograms were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…The covariate importance assessments ( Figure 6) revealed that iron (Fe), manganese (Mn), and magnesium (Mg) were the most influential variables for both RF and GB. For iron (Fe) specifically, high influence on soil pH was expected according to the relevant literature [18,24]. Among the environmental variables, altitude was the one with the higher score for both ML models.…”
Section: Performance Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The covariate importance assessments ( Figure 6) revealed that iron (Fe), manganese (Mn), and magnesium (Mg) were the most influential variables for both RF and GB. For iron (Fe) specifically, high influence on soil pH was expected according to the relevant literature [18,24]. Among the environmental variables, altitude was the one with the higher score for both ML models.…”
Section: Performance Assessmentmentioning
confidence: 99%
“…It controls soil fertility, regulates soil biogeochemical processes, and influences the structure and functioning of terrestrial ecosystems [22]. Regarding its spatial distribution, soil pH seems to be affected by terrain elevation [23] and exhibits spatial cross correlation with other elements, like soil Fe [24]. Based on the above characteristics, soil pH was considered the ideal soil parameter for the current study.…”
Section: Introductionmentioning
confidence: 99%
“…The UKRG method uses the assumption that the spatial variation of z is dependent on three components: a data set structure, a correlated random component, and a residual error. This is a hybrid method, where the spatial trend is measured by polynomial surfaces of different orders, derived globally or locally [45]:…”
Section: Simple Kriging (Krg)mentioning
confidence: 99%
“…In applied geostatistics, experimental variograms are approximated by the theoretical variogram models [22]. Some commonly used theoretical models mainly include the exponential, the spherical, and the Gaussian models [23].…”
Section: N)mentioning
confidence: 99%